Has the Internet Increased Exports for Firms from Low and Middle-Income Countries? - Clarke, George R. G. (2012)
Many commentators have suggested that the internet is one of the forces driving globalization. This paper assesses one aspect of these claims, looking at whether internet access appears to affect the export performance using data from enterprises in low and middle-income economies in Eastern Europe and Central Asia. The paper finds a strong correlation between exporting and internet access at the enterprise level. Moreover, this correlation remains after controlling factors that might affect both exports and internet connectivity and self-selectivity.